2011
DOI: 10.1002/esp.2245
|View full text |Cite
|
Sign up to set email alerts
|

Bedload tracing in a high‐sediment‐load mountain stream

Abstract: International audienceThis paper reports a radiofrequency identification (RFID) tracing experiment implemented in a high-sedimentload mountain stream typical of alpine gravel-bed torrents. The study site is the Bouinenc Torrent, a tributary to the Bléone River in southeast France that drains a 38.9-km² degraded catchment. In spring 2008, we deployed 451 tracers with b-axis ranging from 23 to 520 mm. Tracers were seeded along eight cross-sections located in the upstream part of the lowest 2.3 km of the stream. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
108
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 36 publications
8
108
0
Order By: Relevance
“…2a). The corresponding distribution of travel distances is strongly skewed towards the direction of propagation, a feature commonly observed in field experiments (Liébault et al, 2012;Phillips and Jerolmack, 2014).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…2a). The corresponding distribution of travel distances is strongly skewed towards the direction of propagation, a feature commonly observed in field experiments (Liébault et al, 2012;Phillips and Jerolmack, 2014).…”
mentioning
confidence: 69%
“…Most field campaigns involve a few hundreds of tracer peebles at best (Liébault et al, 2012;Phillips and Jerolmack, 2014). As the tracers spread over kilometers, their concentration rapidly decreases to immeasurable levels.…”
Section: Location Size and Symmetry Of The Plumementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, RFID tracking of natural sediment in streams has faced significant limitations due to the difficulty of drilling holes in natural sediment to imbed the PIT tags. Clasts very commonly failed structurally during drilling operations to insert a PIT tag or magnetic tracer (Liébault et al 2011;Hodge et al 2011), with failure rates of ∼66% reported by Bradley and Tucker (2012). Failure occurs in both soft sedimentary rocks (Liébault et al 2011) and crystalline rocks, which commonly fail along grain boundaries or metamorphic fabrics (Bradley and Tucker 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clasts very commonly failed structurally during drilling operations to insert a PIT tag or magnetic tracer (Liébault et al 2011;Hodge et al 2011), with failure rates of ∼66% reported by Bradley and Tucker (2012). Failure occurs in both soft sedimentary rocks (Liébault et al 2011) and crystalline rocks, which commonly fail along grain boundaries or metamorphic fabrics (Bradley and Tucker 2012). There is a risk of serious injury from flying debris due to catastrophic failure of clasts during drilling.…”
Section: Introductionmentioning
confidence: 99%